Gambaran Lingkungan Fisik Rumah Penderita Penyakit Tb Paru - Bulan, Adiba; Ashari, Agus Erwin; Akbar, Fajar; Ahmad, Haeranah (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
Pulmonary tuberculosis is an infectious and contagious disease caused by Mycobacterium tuberculosis and the lung organs are attacked by these bacteria. Tuberculosis treatment must be optimal and thorough so as not to cause various complications and even death in sufferers. Transmission of tuberculosis is greater in patients with AFB (+) pulmonary tuberculosis. Humidity, temperature, lighting and occupancy density as part of several risk factors for the physical environment of the house are excellent means of transmission of pulmonary TB when air conditions do not meet the requirements. The purpose of this study was to describe the physical environment of the house with the incidence of pulmonary tuberculosis. This research method is descriptive research, measuring and directly observing the physical condition of the house to find out the description of the incidence of pulmonary tuberculosis (tuberculosis).The results of this study show that the density of residents who do not meet health requirements is 118 houses (97.5%). Roomization or room division that met the requirements was 118 houses (97.5). Room ventilation that does not meet health requirements is 83 houses (68.6%). Lighting that did not meet the requirements was 89 houses (73.6%).The conclusion in this study is that the condition of occupant density, ventilation and lighting does not meet the requirements and only roomization is eligible. Pulmonary TB disease.